Arabs in the mirror : images and self-images from pre-Islamic to modern times - Rejwan, Nissim (University of Texas Press, 2008)
To bring new perspectives to the question of Arab identity, Iraqi-born scholar Nissim Rejwan has assembled this collection of writings of Arab and Western intellectuals, who try to define what it means to be Arab. He begins with pre-Islamic times and continues to the last decades of the 20th century.